First year of floodplain forest restoration at the bottom of the former Kakhovka reservoir (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Question: How did the floodplain forests develop at the bottom of the former Kakhovka reservoir during the first year of their existence? Location: Kakhovka Reservoir, Kherson and Zaporizhzhia regions, Ukraine Materials and methods: field research, vegetation sampling with biodiversity plot methodology (Dengler et al. 2016), biomass and size measurement (Pérez-Harguindeguy et al. 2016) Nomenclature: POWO 2024, Mucina et al. 2016, Dubyna et al. 2019, Guiry & Guiry 2024 Results: On the territory of the former Kakhovka reservoir, six nested plot series were established in the thickets dominated by willows and poplars. Salix × rubens is the most common species in the overgrowth of the former Kakhovka reservoir land. The average density of S. × rubens seedlings in the first weeks of their formation reached 90 individuals per 1 m2. In the autumn of 2023, it decreased by 4 times, but their cover increased by dozens times. This was due to the extremely rapid growth of S. × rubens – in the first year the growth rate was about 2.3 cm per day. In autumn, the average height of the willow thickets was about 2 m, with a maximum measured height of 3,09 m. At the same time, branching was observed on some shoots, which is identified as an imature stage of development. In the second year, S. × rubens individuals enter the virgin stage, when the height of willows in moist, rich conditions averaged almost 3,5 m and reached a maximum of 4,7 m. The development of Populus nigra, which mostly grows on dry sandy sediments, is slower and the height and branching of shoots are lower. In the first year, the biomass of S. × rubens exceeded the known values for three-year-old energy willow. A total of 87 species, included 79 – vascular plants, 6 – algae and 2 – mosses were recorded in the six monitoring plots. The average number of species in the annual community was 28 plant species per 100 m2. Conclusions: Our field studies have shown that habitat type G1.11 Riverine Salix woodland, which is protected under Resolution 4 of the Bern Convention and has a high conservation, ecological, economic and recreational value, was forming extremely rapidly and on a large area on the bottom of the former Kakhovka reservoir. This raises the question of the economic feasibility, morali-ty and legality of the possible destruction of this habitat in the event of the future reconstruction of the Kakhovka reservoir, as such proposals are not only con-stantly being voiced from various sides, but also certain decisions are being made at the level of the Ukrainian government without any analysis of possible alternatives, thorough calculation of environmental consequences and economic justification.
Keywords: biodiversity, monitoring plots, willow and poplar thickets, war, Ukraine